Pelaksanaan Program Usaha Kesehatan Sekolah (UKS) di Sekolah Dasar Negeri - Nasruloh, Mahfud Amin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this research is to examine elementary school of Alian Kebumen district UKSprogram’s implemented on 2015/2016 academic year. Methods of data collection using the questionnaire to take primary data and documentation to take on secondary data. Data wereanalyzed by using of percentage’s descriptive statistical analysis. The results showed: 1) Healtheducation: 88% with a very good category. This is showed by school already gives healthyliving habit’s knowledge regularly and responsible for their own health. 2) Health Care: 73%of good category. Schools have scouted the student’s growth and development and gave immunizationto students from related units. 3) Healthy school life’s environment: 68%. This isshowed by high conducive learning environment’s awareness, awareness of keeping the environmentof the school. It is just had limited facilities and supporting infrastructure for UKSprogram’s implementation. It can be concluded that elementary school of Alian Kebumendistrict UKS program’s implemented on 2015/2016 academic year goes well with an averagepercentage of 78%.